Urinary Calcium Excretion Pattern in Preeclampsia - Rai, Snigdha; Upadhyaya, I; Malla, Karishma; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2017)
Aim: This study aimed to evaluate the urinary calcium excretion pattern in preeclampsia and to establish the relation between severity of preeclampsia and urinary calcium excretion Methods: This was a case-control study conducted at Paropakar Maternity and Women’s Hospital, Kathmandu from January to June 2015. There were 88 patients equally divided in each group. 24 hours urine calcium was analyzed by ortho-cresophthalin-complexone method (OCPC) and urinary proteinuria was analyzed bedside by sulphosalicylic acid. Results were analyzed using SPSS 17. P value of < 0.05 was considered as significant. Results: Preeclampsia was found to occur commonly among the nulliparous patients (59%). The patients with MAP with ≥ 110mmHg excreted less calcium in their urine in comparison to the patient with MAP < 110mmHg (73.55mg/24 hrs VS 92.79 mg/24 hr). Daily calciuria was decreased with the increase in proteinuria (91.43 mg, 76.19mg and 54.02mg in 1+, 2+ and 3+ respectively). The 24 hours urine calcium excretion in term preeclamptic patient was significantly reduced in compared to the normotensive term pregnant women (77.92 mg ± 48.61mg VS 117.66mg ±69.21 mg, p <0.001). Conclusion: Preeclamptic patients excrete significantly lower amounts of calcium in urine and it may be a marker of the severity of preeclampsia.